ASSESSMENT OF STUDYING IN FUTURE AVIATION SPECIALISTS’ PROFESSIONAL PREPARATION AS FACTOR OF QUALITY IMPROVEMENT - Plachynda, Tetiana; Moskalenko, Olena (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
In the article it was highlighted the problem of quality improvement of future aviation specialists’ professional preparation in the context of flight safety. The system of students’ educational results assessment was analysed and it was compared to the national grading system, 100-grading system and ECTS rating scale. It was offered rating assessment of students’ educational activity at flight educational establishments.